2001
DOI: 10.1128/jcm.39.7.2576-2580.2001
|View full text |Cite
|
Sign up to set email alerts
|

O-Antigen Diversity among Acinetobacter baumannii Strains from the Czech Republic and Northwestern Europe, as Determined by Lipopolysaccharide-Specific Monoclonal Antibodies

Abstract: O-antigen-specific monoclonal antibodies (MAbs) are currently being generated to develop an O-serotyping scheme for the genus Acinetobacter and to provide potent tools to study the diversity of O-antigens among Acinetobacter strains. In this report, Acinetobacter baumannii strains from the Czech Republic and from two clonal groups identified in Northwestern Europe (termed clones I and II) were investigated for their reactivity with a panel of O-antigen-specific MAbs generated against Acinetobacter strains from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…ST15 is phylogenetically linked with European hospital clone I (15,35), which is associated with epidemic behavior and multidrug resistance (31,35,47). Although at least 39 sequence types of A. baumannii were distinguished among the military outbreak strains (15), four of them (ST11, ST14, ST16, and ST10) accounted for over half of the isolates, suggesting either that the outbreak was clonal in nature or that particular sequence types of A. baumannii are more likely to cause human infection.…”
Section: Discussionmentioning
confidence: 99%
“…ST15 is phylogenetically linked with European hospital clone I (15,35), which is associated with epidemic behavior and multidrug resistance (31,35,47). Although at least 39 sequence types of A. baumannii were distinguished among the military outbreak strains (15), four of them (ST11, ST14, ST16, and ST10) accounted for over half of the isolates, suggesting either that the outbreak was clonal in nature or that particular sequence types of A. baumannii are more likely to cause human infection.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that the A. baumannii OAg region is highly heterogeneous as numerous LPS glycoforms have been defined using both structural and antibody-based studies (21,(26)(27)(28)(41)(42)(43)(44). Although the structural analyses of A. baumannii LPS determined that this organism expresses an S-form LPS, phenotypic analyses of the molecules has been challenging because the OAg cannot be visualized following gel electrophoresis.…”
mentioning
confidence: 99%
“…This will enable us to provide a complete O-serotyping scheme for these species, as has been successfully established for many other clinically significant gram-negative bacteria. Moreover, as has been reported in a recent study (27), such MAbs also have the potential to be employed as a means to define the prevalence of Acinetobacter serotypes in clinical settings and for the facile tracing of strains causing outbreaks in hospitals.…”
Section: Discussionmentioning
confidence: 89%
“…Due to the increased importance of Acinetobacter in the clinical environment and the lack of a reliable phenotypic method for the unambiguous identification of all members of the genus to the species level, we have focused on the development of an O-serotype-based identification scheme for Acinetobacter. Ongoing studies (22)(23)(24)(25)(26)(27) have been centered mainly on the generation of O-antigen-specific monoclonal antibodies (MAbs) against strains belonging to the A. calcoaceticus-A. baumannii complex, but to date, these antibodies have been tested only on small numbers of clinical isolates within a limited geographical range.…”
mentioning
confidence: 99%